The Impact of Environmental Uncertainty and Sense of Urgency on Individual Innovation in Bali's Renewable Energy Startups - Suryandari, Ratnawati Yuni; Muhtadi, Muhamad Ammar; Pahrijal, Rival (West Science Interdisciplinary Studies, 2025)
This study investigates the impact of environmental uncertainty and sense of urgency on individual innovation in renewable energy startups in Bali. In dynamic and resource-constrained startup environments, the ability to innovate is critical for survival and competitiveness. A quantitative approach was employed, surveying 130 respondents from various renewable energy startups using a Likert-scale questionnaire. Data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS 3) to test hypothesized relationships. The results indicate that both environmental uncertainty (β = 0.342, p < 0.001) and sense of urgency (β = 0.540, p < 0.001) significantly influence individual innovation. Furthermore, sense of urgency partially mediates the effect of environmental uncertainty on innovation, highlighting its role as a psychological catalyst that translates external pressures into actionable innovative behaviors. The findings provide theoretical contributions by integrating contingency theory and self-determination theory, and offer practical implications for startup managers and policymakers seeking to foster innovation in uncertain renewable energy markets.